REVIEW OF SIX SIGMA - Rabiae Saidi & Aziz Soulhi (International Journal of Research Science and Management, 2016)
This article focuses on the criticism of the Approach The Six Sigma in showing a few weak points of the Approach The Six Sigma and that it cannot be applied regardless of the problematic, we focus on this observation in taking as real case, maintenance and in particular when it is the reliability of industrial equipment.